Model Pembelajaran Scaffolding Terhadap Kemampuan Pemahaman Matematis Siswa - Wahyuni, Septia; Rahmadhani, Elfi; Azis, Abdul (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2022)
The ability to understand mathematics is an ability that must be possessed by students. With good understanding skills, students will be able to solve both simple and complex problems. Scaffolding learning model is a learning model that provides sufficient assistance to students according to the difficulties they face. The method used in this research is an experimental method with a quantitative approach to class VIII students of SMP Negeri 18 Takengon. Data analysis using t-test of two independent samples. Based on the results of the study, it was found that the scaffolding learning model affected the students' mathematical understanding ability.